Monitoring dynamic networks: A simulation‐based strategy for comparing monitoring methods and a comparative study. (7th July 2021) - Yu, Lisha; Zwetsloot, Inez Maria; Stevens, Nathaniel Tyler; Wilson, James David; Tsui, Kwok Leung
Abstract: Recently, there has been a lot of interest in monitoring and identifying changes in dynamic networks, which has led to the development of a variety of monitoring methods. New methods are often designed for a specialized use‐case and rarely compared to competing methods in a systematic fashion. In light of this, the use of simulation is proposed to compare the performance of network monitoring methods over a variety of dynamic network changes. Using the family of simulated dynamic networks, the performance of several state‐of‐the‐art social network monitoring methods from the literature are compared. Their performance over a variety of types of change is compared; both increases in communication levels as well as changes in community structure are considered. It is shown that there does not exist one method that is uniformly superior to the others; the best method depends on the context and the type of change one wishes to detect. As such, it is concluded that a variety of methods are needed for network monitoring and that it is important to understand in which scenarios a given method is appropriate.